Sulfur heterogeneity: A non-negligible factor in manipulating growth and lipid accumulation of Scenedesmus obliquus at a relatively high ratio of carbon to nitrogen - Liu, Xiang; Zhang, Jin; Lin, Yu; Wei, Lin; Cheng, Haomiao; Wang, Min (Bioresource technology, 2022)
[Display omitted] •Algal growth was boosted by various forms of sulfur with different dose dependent.•Effect of nitrogen on carbon assimilation in cells was regulated by sulfur form.•Sulfate was more beneficial to increase lipid productivity than other form.•Sulfur induced changes in expression of genes encoding lipid-related enzymes. Algal biodiesel has been becoming a focus in the field of bioenergy worldwide. In this study, effects of heterogeneous sulfur (SO42-, SO32- and S2-) on growth and lipid accumulation of Scenedesmus obliquus cultured in wastewater with a C/N ratio of 30 were investigated, respectively. The results shown that SO42-, the optimal sulfur source, could trigger cell growth in a concentration-dependent manner. However, SO32- was superior to the others in boosting carbon uptake of cells, which was subject to NH4+-N concentration. Only SO42- could simultaneously increase lipid content and productivity of cells with a dominant component of oleic acid (C18:1n9c) occupying approximately 40% in fatty acid profile. Additionally, the genes encoding enzymes such as CDIPT, ADPRM, DPP1, pmtA and BTA1 involved in the uppermost lipid-related pathway (glycerophospholipid metabolism) were identified facing different sulfur source regardless of the concentration changes. These findings may facilitate nutrition management efforts to enhance microalgae-based biofuel production.